Contemporary art the essential guide to 200 groundbreaking artists - Bonham-Carter, Charlotte; Hodge, David; Bonham-Carter, Charlotte (Gooddman, 2013)
Over the years ambitious redevelopments and constructions conceived specifically for contemporary art - such as London's Tate Modern, Centre Pompidou in Paris and Museo Guggenheim Bilbao - have attracted record numbers of visitors. This guide pinpoints key artists and events, and helps demystify a generation of rapid change in the art world.